Numerical analysis of multicomponent suspension droplets in high-velocity flame spray process - Gozali, E.; Mahrukh, Mahrukh; Gu, Sai; Kamnis, S. (Springer Science Business Media, 2014)
The liquid feedstock or suspension as a different mixture of liquid fuel ethanol and water is numerically studied in high-velocity suspension flame spray (HVSFS) process, and the results are compared for homogenous liquid feedstock of ethanol and water. The effects of mixture on droplet aerodynamic breakup, evaporation, combustion, and gas dynamics of HVSFS process are thoroughly investigated. The exact location where the particle heating is initiated (above the carrier liquid boiling point) can be controlled by increasing the water content in the mixture. In this way, the particle inflight time in the high-temperature gas regions can be adjusted avoiding adverse effects from surface chemical transformations. The mixture is modeled as a multicomponent droplet, and a convection/diffusion model, which takes into account the convective flow of evaporating material from droplet surface, is used to simulate the suspension evaporation. The model consists of several sub-models that include premixed combustion of propane-oxygen, non-premixed ethanol-oxygen combustion, modeling of multicomponent droplet breakup and evaporation, as well as heat and mass transfer between liquid droplets and gas phase.